Factors influencing Community Healthcare Worker’s adoption of mobile health technology (mhealth): A case of sangini supportive supervision (sangini) app, Uttar Pradesh, India - Juneja, Sabhya; Kumar, Archna (Indian Journal of Community Health, 2021)
Background: Community Health Workers (CHWs) are agents in delivering primary healthcare. mhealth is being used to improve their performance. However, there are little evidences on factors influencing adoption of technology. Henceforth, sangini app was undertaken for analysis. Objective: To investigate factors of adoption of sangini app among users and non-users. Methods & statistical analysis: Constructs from Technology Acceptance Model (TAM) and Theory of Self-Efficacy (SE) were used as tools for study. The study used an experimental study design Kaushambi and Pratapgarh districts of Uttar Pradesh (U.P.), India was selected as intervention and control groups respectively. The study sample consisted of CHWs i.e. 90 Sangini and 270 ASHAs. Two sample t test with equal variances and univariate regression analysis was applied. Results: TA and SE were predicators however; individual characters didn’t impact adoption of mhealth. Conclusion: There is need to comprehend factors influencing adoption of mhealth to improve performance of CHWs.